2018
DOI: 10.3847/1538-4357/aac6eb
|View full text |Cite
|
Sign up to set email alerts
|

How Galaxies Form Stars: The Connection between Local and Global Star Formation in Galaxy Simulations

Abstract: Using a suite of isolated L galaxy simulations, we show that global depletion times and star-forming gas mass fractions in simulated galaxies exhibit systematic and well-defined trends as a function of the local star formation efficiency per freefall time, ff , strength of stellar feedback, and star formation threshold. We demonstrate that these trends can be reproduced and explained by a simple physical model of global star formation in galaxies. Our model is based on mass conservation and the idea of gas cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 96 publications
5
87
0
Order By: Relevance
“…Motivated by Semenov et al (2018) and Lupi (2019), we also include an additional fiducial boost to the radial momentum of a factor of two.…”
Section: Sub-grid Physical Processes Includedmentioning
confidence: 99%
“…Motivated by Semenov et al (2018) and Lupi (2019), we also include an additional fiducial boost to the radial momentum of a factor of two.…”
Section: Sub-grid Physical Processes Includedmentioning
confidence: 99%
“…After all, feedback is not instantaneous with star formation, as ionizing radiation is injected for upwards of 10 Myr (Leitherer et al 1999), supernova feedback is not felt for the first ∼ 5 Myr, and then continues stochastically for ∼ 30 Myr (Agertz et al 2013). The timescales for feedback injection are not coincidentally on the order of the lifetimes of star forming regions themselves in the feedback regulated model (Oklopčić et al 2017;Semenov et al 2018;Grudić et al 2018). Star formation equilibrium need not be expected, even at the 10 6 M giant molecular cloud (GMC) scale.…”
Section: Introductionmentioning
confidence: 99%
“…steady state) in some averaged sense, that it is locally in some dynamical equilibrium where the ISM is in a constant cycle of collapse, star formation, and cloud destruction/feedback. It is thus never instantaneously in local equilibrium, and is constantly oscillating between those phases (Benincasa et al 2016;Semenov et al 2017Semenov et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Star formation on large scales could be entirely selfregulated by stellar feedback, as advocated by Ostriker et al (2010) and Hopkins et al (2014). In a seminal albeit recent paper, Semenov et al (2018) have shown that once the star formation efficiency at small scale is large enough (typically larger than 1%), the global depletion time converges to a fixed value set by stellar feedback only (therefore independent of ff ).…”
Section: Introductionmentioning
confidence: 99%